Applying REAP (Read, Encode, Annotate, Ponder) Learning Method to Improve the Students’ Reading Literacy - Lian Brilian; Sri Damayanti; Opik Dwi Indah; Iin Dwi Aristy Putri; Alim Surya Saruman (Institut Agama Islam Negeri Palopo, 2022)
This research is a Classroom Action Research (CAR) conducted at SDN 104 Wiwitan which aims to improve students' reading literacy of class V in Indonesian learning through the REAP learning method. The sample of this research is 30 students in academic year 2021/2022. The instruments used to get the data are observation and test. Data analysis used quantitative and qualitative descriptive statistics. The result of this research showed that the average value of students in the first cycle was 51% with a classical learning percentage of 13%, and in the second cycle the average value obtained by students was 85% with a percentage of 93%. Judging from these data, it can be concluded that there is an enhancement in students' reading literacy in Indonesian learning after they being taught using REAP (Read, Encode, Annotae, Ponder) method, where from cycle I to cycle II it increased by 34%.